Understanding real and mythical cancer risk factors: Insights from a university-based study - Senay Yildirim-Kahriman; Gulay Yildirim; Selmin Kose (PLoS ONE, 2025)
Despite extensive research on cancer etiology, many cancers remain associated with preventable risk factors. Raising public awareness of these factors is critical for promoting preventive behaviors. This study aimed to assess university students’ awareness of both scientifically validated and mythical cancer causes, to identify sociodemographic and health/lifestyle-related factors associated with awareness levels, and to examine the relationship between awareness of evidence-based and mythical cancer risk factors. A cross-sectional survey was conducted among 896 students from three Universities in Turkey. Data were collected using a Personal Information Form, the Cancer Awareness Measure (CAM) and Cancer Awareness Measure – Mythical Causes Scale (CAM-MYCS), which evaluates belief in widely held but scientifically unsubstantiated cancer causes (e.g., microwave ovens, stress, artificial sweeteners, electromagnetic frequencies). Statistical analyses included descriptive statistics, Spearman’s correlation, and multiple linear regression. Participants demonstrated significantly higher awareness of scientifically established cancer causes (70.7%) compared to mythical ones (10.2%). A moderate negative correlation was observed between CAM and CAM-MYCS scores (r = −0.511; p < 0.001), indicating that increased awareness of real causes is associated with decreased belief in myths. Regression analysis revealed that CAM scores were significantly predicted by academic year, being in the normal Body Mass Index (BMI) spectrum, and by having attended an oncology course (R² = 0.142; p < 0.001), whereas CAM-MYCS scores were predicted by academic year and high BMI values (R² = 0.072; p < 0.001). These findings highlight the need for targeted educational interventions aimed at both enhancing awareness of factual cancer risk factors and correcting persistent misconceptions. The results provide valuable insights for university-based public health initiatives seeking to improve cancer literacy and promote preventive health and lifestyle behaviors among young adults.